Acceleration of metal-atom diffusion in electric field at metal/insulator interfaces: First-principles study. (12th March 2018) - Nagasawa, Riki; Asayama, Yoshihiro; Nakayama, Takashi
Abstract: Metal-atom diffusion from metal electrodes into SiO2 in electric fields was studied using first-principles calculations. It was shown in the case without electric field that the diffusion barrier of a metal atom is mainly made of the cohesive energy of bulk metal layers, while the shape of the diffusion potential reflects the hybridization of the metal-atom state with metal-induced gap states (MIGSs) and the electron transfer between the metal atom and the electrode. We found that the metal-atom diffusion is markedly accelerated by the applied electric field, such that the diffusion barrier ϕB ( E ) decreases almost linearly with increasing electric field strength E . By analyzing the physical origins of the metal-atom diffusion, we derived the universal formula to estimate the diffusion barrier in the electric field, which is closely related to MIGSs.